Experience in Performing Bidirectional Cavopulmonary Anastomosis in the Surgical Treatment of Tricuspid Atresia - Dziuryi, Ivan V.; Truba, Iaroslav P.; Prokopovych, Liliya M.; Fylypchuk, Vasyl V.; Lazoryshynets, Vasyl V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Tricuspid atresia (TA) is a rare cyanotic congenital heart disease (CHD) first described by Kreysig (1817). Bidirectional cavopulmonary anastomosis (BCPA) is part of the hemodynamic correction of such a complex combined CHD. In patients after BCPA, blood flow through the superior vena cava, providing efficient pulmonary blood flow, is the most important factor influencing blood oxygen saturation. The aim. To evaluate perioperative characteristics of the patients, immediate and long-term results after BCPA with TA. Materials and methods. In the period from January 1996 to April 2022, 50 patients with TA and multiple concomitant CHD underwent hemodynamic correction at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. There were 27 male patients (54%) and 23 female patients (46%). The mean age of the patients at the time of surgery was 31.6 ± 17.2 months (from 6 to 144 months). The main method of diagnosis in determining the defect and assessing the immediate and long-term results was echocardiographic examination and probing of the heart cavities. Among the 50 patients surveyed, 17 children were older than 2.5 years, so all the subjects were divided into 2 age groups: group I (n = 33) up to 2.5 years, group II (n = 17) older than 2.5 years to determine the optimal time of hemodynamic correction based on immediate and long-term results. Results. In the early postoperative period, there were 2 (4%) deaths among the patients of group II. The cause of death was acute heart failure in one case and infectious factor which led to the development of sepsis in another. There was a very interesting trend of increase in the duration of the operation (min): 239 ± 73.3 in group I, 251 ± 68.5 in group II; duration of mechanical ventilation (hours): 5.3 ± 1.4 in group I, 11 ± 3.7 in group II; duration of exudation (hours): 67 ± 22.9 in group I, 76 ± 26.8 in group II. There was significantly higher average dose of sympathomimetic (μg/kg/hour): 5 ± 2.1 for 60 ± 21.4 (hours) in group I; 7 ± 4.5 for 84 ± 29 (hours) in group II, hospital stay (days): 18 ± 5.7 in group I, 22 ± 11.3 in group II. Significantly lower mean systemic saturation at discharge 81 ± 4.6 (%) which was reported in children of group II compared to those of group I 88 ± 3.4 (%) clearly shows a decrease in the contribution of superior vena cava flow into the systemic circulation depending on the patient’s age, therefore, the clinical effect of performing BCPA as a stage of single-ventricular correction in patients with TA is much better when performing surgery in early childhood. Early postoperative period was uneventful in 27 (54%) patients. The other 23 (46%) patients of both groups had 16 and 18 complications in 10 (20%) patients of group I and 13 (26%) patients of group II, respectively, due to adverse factors of preoperative condition and specific changes in blood circulation characteristic of the BCPA. During the observation period lasting 49 ± 23.5 months, from 6 to 180 months, the final stage of hemodynamic correction was examined and performed: total cavopulmonary anastomosis was created in 31 (65%) patients. No deaths were reported after the final stage of hemodynamic correction. Conclusions. The contribution of superior vena cava flow to total cardiac output is directly related to the patient’s age and gradually decreases in the elderly, which indicates a decrease in systemic saturation, so the clinical effect of BCPA as a stage of single ventricular correction in patients with TA is much better when performing surgery in early childhood.